2009
DOI: 10.1073/pnas.0812528106
|View full text |Cite
|
Sign up to set email alerts
|

The human Dcn1-like protein DCNL3 promotes Cul3 neddylation at membranes

Abstract: Cullin ͉ DCUN1D ͉ Nedd8 ͉ ubiquitin ͉ squamous cell carcinoma-related oncogene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 27 publications
8
90
2
Order By: Relevance
“…To provide further evidence, we studied the localization of CUL3 in HeLa cells. In these cells, CUL3 must be recruited from the nucleus to the cytoplasm, where it is neddylated and activated (13). Here, we confirmed that CUL3 was predominantly nuclear in unstimulated HeLa cells and recruited to the cytoplasm when KLHL3 was cotransfected.…”
Section: And Colleaguessupporting
confidence: 72%
“…To provide further evidence, we studied the localization of CUL3 in HeLa cells. In these cells, CUL3 must be recruited from the nucleus to the cytoplasm, where it is neddylated and activated (13). Here, we confirmed that CUL3 was predominantly nuclear in unstimulated HeLa cells and recruited to the cytoplasm when KLHL3 was cotransfected.…”
Section: And Colleaguessupporting
confidence: 72%
“…Nevertheless, the role of the five DCN orthologues in mammals remains largely unknown. The PONY domains of the individual family members can activate several cullin-RBX pairs to varying degrees, but the impact on in vivo neddylation has been difficult to assess with RNA interference, probably because of at least partial redundancy among the various DCN family members [63,64]. …”
mentioning
confidence: 99%
“…Similarly, it has been shown that DCNL3 knockdown stabilizes the CUL3 substrate NRF2 (37). DCNL1, DCNL2 (long isoform), and DCNL3 have been shown to be promiscuous in their ability to bind multiple cullins (37). Although there is promiscuity among DCNL members in binding to CUL2, DCNL1 was most associated with neddylated CUL2, followed by DCNL3 (see Fig.…”
Section: Resultsmentioning
confidence: 98%
“…DCNL1 promotes neddylation of CUL2 (Fig. 2) as well as other cullins (12), and the engagement of HIF1␣ to ECV has been shown previously to promote CUL2 neddylation (27,37). We asked whether substrate-mediated CUL2 neddylation is coordinated with DCNL1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation